2005
DOI: 10.1587/elex.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Switching characteristics of SiC JFET and Schottky diode in high-temperature dc-dc power converters

Abstract: This paper reports on SiC devices operating in a dc-dc buck converter under extremely high ambient temperatures. To this end, the authors packaged SiC JFET and Schottky diodes in thermally stable packages and built a high-temperature inductor. The converter was tested at ambient temperatures up to 400 • C. Although the conduction loss of the SiC JFET increases slightly with increasing temperatures, the SiC JFET and Schottky diode continue normal operation because their switching characteristics show minimal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…One of the advantages of unipolar devices is their speed, offering very low commutation losses due to the lack of recovery phenomenon [9]. Their conduction losses, however, are somewhat higher than that of their bipolar counterparts.…”
Section: Unipolar Devicesmentioning
confidence: 99%
“…One of the advantages of unipolar devices is their speed, offering very low commutation losses due to the lack of recovery phenomenon [9]. Their conduction losses, however, are somewhat higher than that of their bipolar counterparts.…”
Section: Unipolar Devicesmentioning
confidence: 99%
“…SiC in particular has been seen as an ideal semiconductor material for high voltage power devices, due to its high critical breakdown electric field and large thermal conductivity [2,3]. We have focused on the high temperature operational capabilities of SiC devices, and studied the switching behavior of SiC Schottky barrier diodes (SBD) and JFETs under extremely high ambient temperature [4,5,6]. We have also clarified the junction capacitance-reverse bias voltage (C-V) characteristics of SiC devices for the entire rated voltage range, and related these to the device structure and process parameters [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of SiC power switching semiconductor devices have been researched and developed in an effort to reduce loss in power conversion circuits, and also to establish additional functionality in energy usage by overcoming the limitations stemming from conventional Si power devices. Lorenz et al and B. Ozpineci et al presented the reduction of switching loss in a converter circuit by applying a high voltage SiC Schottky barrier diode [1,2], and T. Funaki et al reported the power conversion circuit operation in high temperature ambient (450 • C) with SiC JFET [3,4]. However, the evaluation of SiC power device for large current application circuit has not been sufficiently discussed due to the difficulty in manufacturing defect-free large area SiC device.…”
Section: Introductionmentioning
confidence: 99%